Supporting the Social Lives of Secondary Students With Severe Disabilities: Considerations for Effective Intervention. (March 2018) - Carter, Erik W.
For adolescents with severe disabilities, efforts to enhance the social dimensions of schooling are widely advocated, yet rarely implemented. The peer interactions and relationships so critical to school success and individual well-being can be elusive for many students with intellectual disability, autism, and multiple disabilities. This article highlights promising approaches for enhancing the social lives of secondary students with severe disabilities. The author presents five areas of intervention for secondary schools: student-related factors, peer-related factors, support-related factors, opportunity-related factors, and context-related factors. Attention then turns to how various peer-mediated approaches—peer support arrangements, peer network interventions, and peer partner programs—can be drawn upon to address one or more of these important factors. Recommendations are offered for (a) implementing multicomponent interventions, (b) addressing fidelity in the context of individualized interventions, (c) measuring the social-related impact, (d) promoting changes in social outcomes that have widespread and long-term impact, and (e) encouraging schoolwide and sustained adoption of these approaches.